2013
DOI: 10.1021/ie400686d
|View full text |Cite
|
Sign up to set email alerts
|

Acetalization of Carbonyl Compounds with Pentaerythritol Catalyzed by Metal(IV) Phosphates as Solid Acid Catalysts

Abstract: In the present endeavor, amorphous cerium phosphate (CP) and thorium phosphate (TP) have been synthesized by the sol–gel method. Further, CP and TP also have been synthesized under microwave irradiation to yield CPM and TPM. The materials have been characterized for elemental analysis (inductively coupled plasma-atomic emission spectrometry, ICP-AES), spectral analysis (Fourier transform infrared spectroscopy, FTIR), thermal analysis (TGA), X-ray diffraction studies, scanning electron microscopy (SEM), energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…23,24 The suction-induced complex S]O improves the electron-accepting ability of the metal atoms, contributing to the formation of supper acid. 27 Thus, 1.55 wt% is sufficient for the esterication reaction. The surface sulphur content is 5.97% (atomic ratio), which is the quantitative estimated by means of XPS.…”
Section: Characterization Of Catalystsmentioning
confidence: 99%
“…23,24 The suction-induced complex S]O improves the electron-accepting ability of the metal atoms, contributing to the formation of supper acid. 27 Thus, 1.55 wt% is sufficient for the esterication reaction. The surface sulphur content is 5.97% (atomic ratio), which is the quantitative estimated by means of XPS.…”
Section: Characterization Of Catalystsmentioning
confidence: 99%
“…The formation of hemiacetal also named as halfway processing to form acetals. The second step produced acetal by reaction of hemiacetal with second alcohol molecule followed with protonation of hemiacetal by an acid catalyst, removal of water, nucleophilic attack by a methanol and the last was the loss of water to form acetal product [2,15,16]. Yusuf et al [16,17] reported the reaction mechanism of acetalization of benzaldehyde and 2-hydroxy benzaldehyde used acid catalysts (HCl) and applied with Hyperchem software.…”
Section: Ab Initio Methods On the Mechanism Of Acetalization Of 2-methmentioning
confidence: 99%
“…The benzaldehyde dimethyl acetal compound is a compound that can be widely used in daily life. The compound has been used as a solvent in the pharmaceutical industry, detergents, varnishes, perfumes, cosmetics, food additives, and beverages (Parangi et al 2013;Li et al 2004). Besides that, acetal can also be used as motor oil, lubricant, hydraulic fluid and as an emulsion for petroleum drilling operations.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with ketones, acetalization is easier between aldehyde and alcohol. The catalysts commonly used in the acetalization reaction are protonic acids, organic metal frame work (MOF) containing thiourea (Luan et al 2014), N-chlorosuccinimide/thiourea (May et al 2009), amorphous cesium phosphate (Parangi et al 2013), copper [Cu3(BTC)2] (Dhakshinamoorthy et al 2010;Jin et al 2014), and UIO 66 (Arrozi et al 2014).…”
Section: Introductionmentioning
confidence: 99%